Test your vocabulary and grammar = (NpEREW)QÆR ZNANNQ Z LEKSIKI TA GRAMATIKI (B: /s)E - (Ns)QÆNELXNIK(B, æ. (Np(B.,s)E; (NkARPUSX(B, (Na(B. (Nk(B.,s; (NoLX[ANSXKIJ(B, (Nd(B. (Nw(B.,s ((NkI)QÇW (B:s)E (NkI)QÇWSXKIJ UNÆWERSITET ÆMENÆ bORISA gRÆN^ENKA(B,s)E, 2012)
(NnAW^ALXNIJ POS)QÆBNIK MAÃ NA METÆ PEREWÆRKU LEKSIKO(B-(NGRAMATI^NOÇ KOMPETENCÆÇ STUDENTÆW(B, (NQKU WONI NABUWA@TX U PROCESÆ OWOLODÆNNQ ANGLÆJSXKO@ MOWO@ WPRODOWV ZDOBUTTQ OSWÆTNXO(B-(NKWALÆFÆKACÆJNOGO RÆWNQ (B"(NBAKALAWR(B".s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NmOWOZNAWSTWOs -- (NaNGL)QÆJSXKA MOWAs)E -- (NgRAMATIKAs -- (NlEKSIKAs; (NGRAMATI^N)QÆ QWI]As)E; (N^ASI W ANGL)QÆJSXKÆJ MOWÆs)E; (NLEKSIKA ANGL)QÆJSXKOÇ MOWIs)E